Mengevaluasi Efektivitas Strategi SEO On-Page dan Off-Page untuk Peningkatan Peringkat Mesin Pencari - Desmantyo, Pandu Sapto; Baswarani, Delfta Tunjung; Utama, Agastya Pandu Satriya; Hasanah, Reisa Nur (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2025)
Search Engine Optimization (SEO) training activities were carried out in the Cibiru Wetan Tourism Village for the reason that the Cibiru Wetan tourist village wanted to participate in the Indonesian Tourism Village Award in the digital village category, and one of the indicators was an increase in traffic visiting the Cibiru Wetan tourist village website and optimization of Search Engine Optimization (SEO) was the solution. It was proven that this assistance was successful in increasing village officials' understanding of digital marketing. Involving 21 participants, this training focused on basic SEO concepts, keyword optimization, content creation and website analysis. Before the training, SEO knowledge was only possessed by one individual, but afterward, all participants showed significant improvements in their understanding and competency, with post-test scores increasing from 20% to 70%. This program also supports target villages in participating in the Indonesian Tourism Village Award (ADWI). This activity emphasizes the importance of digitalization in advancing sustainable tourism, empowering local communities. The results of this training will not only benefit Cibiru Wetan Village but also become a model that can be applied by other villages who want to develop their tourism sector in a sustainable manner.